Emerging Roles of Circular RNAs in Vascular Smooth Muscle Cell Dysfunction - Pu, Zuo; Lu, Jingbo; Yang, Xiaohan (Frontiers in Genetics, 2022)
Atherosclerosis is the major pathophysiological basis of cerebrovascular and cardiovascular diseases. Vascular smooth muscle cells (VSMCs) constitute the main structure of vasculature and play important roles in maintaining vascular tone and blood pressure. Many biological processes and cellular signaling events involved in atherosclerogenesis have been shown to converge on deregulating VSMC proliferation and migration. However, the molecular mechanisms underlying dysfunctional VSMC migration and proliferation in atherosclerosis are still poorly defined. Recent evidence revealed that circular RNAs (circRNAs) are closely related to diseases such as degenerative diseases, tumor, congenital diseases, endocrine diseases and cardiovascular diseases. Several studies demonstrated that circRNAs played critical roles in the regulation of VSMC proliferation and migration. This review describes recent progress in the profiling of circRNAs by transcriptome analysis in VSMCs and their molecular functions in regulating VSMC proliferation and migration.